The Influence of Mis-interpretation on Area Assessment - Joshi, S. C. (Indian Forester, 1972)
Over an area of 4032 Hectar in Lachhiwala forests, forest survey aiming at forest type mapping and area assessment with aerial photographs was carried out in March 1971. Even using old aerial photographs on 1:27500 scale, it was possible to make a forest type map of the area. After stratification field checking for mis-interpretation was also taken up and it was found that out of 39 points which were interpreted as Sal type 37 were correctly interpreted and in case of miscellaneous type out of 9 points only one point was mis-interpreted. Using stastical methods errors in area proportions due to mis-interpretation were worked out and it was found that in Sal type errors due to mis-interpretation were of the order of 4.85% whereas in miscellaneous it went up to 23.56%.